A steerable introducer‐assisted wire‐loop snare technique: A bailout for unsuccessful lead extraction by a Needle's Eye Snare. Issue 5 (9th August 2022) - Isawa, Tsuyoshi; Honda, Taku; Yamaya, Kazuhiro; Toyoda, Shigeru
Abstract : The Needle's Eye Snare (Cook Medical) is an effective tool for extracting leads via a femoral vein. However, it sometimes fails to grasp the lead. We describe an alternative method of successfully grasping a lead by creating a wire‐loop around the lead with the help of a steerable introducer.